Note of incomes in designated areas, 1960 and 1965 - Ross, M (Economic & Social Studies, 1971)
Recently in response to a request from the EEC, incomes were estimated separately for the designated areas and the remainder of the country for i960 and 1965. The results are presented here to make them available to other interested research workers. The designated areas owe their origin to the Undeveloped Areas Act of 1952 which designated certain parts of the country, namely (a) those areas along the western seaboard which formerly came under the jurisdiction of the Congested Districts Boards, and (b) any other areas which, for the time being, might be added to the list of scheduled areas by the Minister for Industry and Commerce as areas in which special efforts would be made to promote industrial development. The statutory body established for this task in 1952 was An Foras Tionscal.
Keywords: Incomes - Ireland; EEC